A10.12 Characterisation of a New mPGES-1 Inhibitor in Human and Murine Models of Inflammation. (25th February 2013) - Leclerc, Patrick; Idborg, Helena; Stenberg, Patrick; Korotkova, Marina; Jakobsson, Per-Johan
Abstract : Background: Microsomal prostaglandin E synthase-1 (mPGES-1) inhibition has been suggested as an alternative to cyclooxygenase (COX) inhibition in the treatment of pain and inflammation. This approach could potentially mitigate the gastro-intestinal and cardiovascular side effects associated to traditional non-steroidal anti-inflammatory drugs (NSAIDs) and Coxibs. Aim: To characterise a selective inhibitor of mPGES-1 and study its impact on the prostanoid profile in various models of inflammation. Materials and Methods: Potency and selectivity: Compound III was incubated with active enzymes of the prostanoid pathway (mPGES-1, COX-1/2, PGIS, H-PGDS). For potential cross-reactivity towards thromboxane synthase, compound III was tested in a thromboxane release assay in platelets. A549 cells: compound III was assayed in both short and long-term assays. Cells were stimulated with IL-1β/TNF-α or IL-1β alone and incubated in the presence of inhibitors. Whole blood assay/mouse peritoneal macrophages: blood and macrophages were induced with LPS and incubated with compound III for 24 h. Air pouch model: the inflammatory reaction was triggered by a carrageenan injection intra-pouch. Inhibitors were injected i.p. and exudates were collected after 6 h. Prostanoid analysis: Prostanoids were measured by mass spectrometry or enzyme immunoassay. Results: Compound III has an IC50 of 0.4 µM and 1 µM in human and murine mPGES-1 respectively. It has no activity on other enzymes of the prostanoid pathway and did not inhibit thromboxane release from human platelets. In cellular assays, it reduced PGE2 production in A549 cells, mouse peritoneal macrophages and LPS-stimulated whole blood. In mouse peritoneal macrophages, compound III caused a shunt to the prostacyclin pathway. Lastly, we assayed compound III in the air pouch model to verify its impact on the prostanoid profile and compare it to the profile obtained in mPGES-1 k.o. mice. As opposed to mPGES-1 genetic deletion, which attenuated PGE2 induction and caused a shunt to the thromboxane pathway, mPGES-1 inhibition with compound III reduced PGE2 production and tended to decrease the levels of other prostanoids. Conclusions: Compound III is an active and selective inhibitor of mPGES-1. Its impact on the prostanoid profile was assay dependent. However, in the air pouch, contrary to mPGES-1 gene deletion, compound III did not trigger shunting, a scenario more likely to represent the outcome of mPGES-1 inhibition at the inflammatory site.